Oblicz pamiętając o kolejności wykonywania działań:
a) 42÷ (-7) + 9-8×√5²-4² (różnica pod wspólnym pierwiastkiem)
b) 4½-½√196 - 5⁰×3³+(½)⁻³
c) 2√64 - 18÷3² - √144
d) 2(√64 -18)÷(2²-√196)
e) 2√64 - 18÷ (3²-√196)
f) 3(√64 - 18) ÷ (4²-√225)
Oblicz:P
g) (3√12-5√48)×(-3√3)
h) (1,8√48-2,4√75)×(-√12)

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-09-28T17:12:19+02:00
A) 42÷ (-7) + 9-8×√5²-4²= -6+9-8x*3=3-24x
b) 4½-½√196 - 5⁰×3³+(½)⁻³= 4,5-0,5*14-1*9+8=4,5-7-9+8=-3,5
c) 2√64 - 18÷3² - √144=2*8-18/9-12=16-2-12=2
d) 2(√64 -18)÷(2²-√196)=2(8-18)/(4-14)=-20/-10=2
e) 2√64 - 18÷ (3²-√196)=2*8-18/-6=16+3=19
f) 3(√64 - 18) ÷ (4²-√225)=3(8-18)/(16-15)=-30

g) (3√12-5√48)×(-3√3)=(6√3-20√3)*(-3√3)=(-14√3)*(-3√3)=126
h) (1,8√48-2,4√75)×(-√12) =(7,2√3-12√3)*(-2√3)=(-4,8√3)*(-2√3)=28,8
2009-09-28T18:11:36+02:00
A) 42÷ (-7) + 9-8×√5²-4² = -6 + 9-8 x 3=-6+9-24=-21
b)-
c) 2√64 - 18÷3² - √144= 2 x 8 - 3 - 12= 1
d) 2(√64 -18)÷(2²-√196)=2 (8-18) ÷ (4-14)= 16-36 ÷-10= -20 ÷ -10= 2
e) 2√64 - 18÷ (3²-√196)= 2×8 - 18 ÷ (9-14)= 16-18÷-5=16- (-3.6)= 16 +3.6=19.6
f) 3(√64 - 18) ÷ (4²-√225)=3 (8-18) ÷ (16-15)= 24 - 54 ÷1 = -30

Oblicz:P
g) (3√12-5√48)×(-3√3)= (3√12-5√12 ×4) x (-3√3)= -7√12 x -3√3=21√48=21√12x4= 42 √12
h) (1,8√48-2,4√75)×(-√12)=-